1983
DOI: 10.1111/j.1476-5381.1983.tb09398.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicotine on locomotor activity in non‐tolerant and tolerant rats

Abstract: 1Rats were tested for locomotor activity in photocell cages, for 80 min starting immediately after subcutaneous injection of (-)-nicotine bitartrate or 0.9%w/vNaCl solution (saline). In nontolerant subjects, nicotine (0.1 to 0.4 mg/kg base) depressed activity and induced ataxia in the first 20 min, but increased activity later in the session; these actions were dose-dependent. 2 Tolerance was studied by comparing rats given nicotine (0.4 mg/kg s.c.) every day with control rats given saline instead. Each week, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
185
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(220 citation statements)
references
References 21 publications
33
185
2
Order By: Relevance
“…Previous studies assessing the acute effects of i.p. nicotine administration upon locomotion have yielded mixed results (either an increase or a decrease have been reported, see Jerome and Sanberg 1987;Clarke and Kumar 1983). Present data suggest an age-related dissociation in nicotine effects, which can possibly be ascribed to age-related discontinuities in the functional maturation of drug-targeted brain systems (Naeff et al 1992;Teicher et al 1995;Trauth et al 1999).…”
Section: Behavioral/pharmacological Effects Of Oral Nicotinementioning
confidence: 72%
“…Previous studies assessing the acute effects of i.p. nicotine administration upon locomotion have yielded mixed results (either an increase or a decrease have been reported, see Jerome and Sanberg 1987;Clarke and Kumar 1983). Present data suggest an age-related dissociation in nicotine effects, which can possibly be ascribed to age-related discontinuities in the functional maturation of drug-targeted brain systems (Naeff et al 1992;Teicher et al 1995;Trauth et al 1999).…”
Section: Behavioral/pharmacological Effects Of Oral Nicotinementioning
confidence: 72%
“…Previous research has shown that acute treatment with nicotine can suppress locomotor activity in rats [7,36,37]. Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, although the shift measures differed statistically, overall activity for HR and LR (number of infrared beam breaks) after acute and chronic administration of nicotine did not differ significantly (Trial 1: HR = 179 ± 18, LR = 152 ± 10; Trial 7: HR = 382 ± 21, LR = 347 ± 12). This latter result is consistent with the z-score analyses; nicotine disrupts predictable individual differences in activity that are present in a drug-free state.We found that mecamylamine (1 mg/kg) completely prevented the acute suppressant and chronic activating effects of nicotine [7,26,37]. The peripheral nACh receptor antagonist hexamethonium, in contrast, did not block the chronic psychomotor effects of nicotine [5,7].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Similarly, nicotine administration also modifies locomotion, anxiety, memory, nociception, and produces rewarding effects in several animal models (Clarke and Kumar, 1983;Hildebrand et al, 1999;Marubio et al, 1999;Picciotto et al, 1995). Neuroanatomical studies have shown a high density of CB1 receptors in neurons of the cerebellum, basal ganglia, limbic cortices, hippocampus, 3 hypothalamus and different nuclei of the extended amygdala (Tsou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%